Correctional Institutions as a Place of Guidance to Counter Radicalism for Terrorist Prisoners in Indonesia - Erlangga Alif Mufti; Edy Lisdiyono; Retno Mawarini Sukmariningsih; David Maharya Ardyantara; Ontran Sumantri Riyanto (Institute of Medico-legal Publications Pvt Ltd, 2022)
Correctional Institution as a place to house terrorist inmates have not managed to solve the problem ofderadicalization to complete for terrorist inmates, so it is necessary to cooperate with other relevant stateinstitutions. But the deradicalization process has obstacles such as inmates being unwilling to cooperate and theabsence of synergy with other applicable state institutions. The parameters of the success of correctional institutionsin conducting deradicalization are necessary to strengthen the process of returning terrorism convicts to thecommunity, so that this research is important to do. This study uses the research method that is juridical normativeby collecting primary data and secondary data. The results of this study describe the correctional institution to bethe vanguard in the process of deradicalization of terrorism convicts to be ready to return to the community so thatthe implementation of effective deradicalization required cooperation from correctional institutions, relevant stateinstitutions, and inmates. Correctional institutions are an important vector in the fight against radicalism. The roleof correctional institutions in the deradicalization of terrorism prisoners is to synergize with other institutions tofoster terrorist prisoners to become good human beings when they leave correctional institutions.